2010
DOI: 10.1123/ijsnem.20.6.457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Purported Aromatase and 5 α-Reductase Inhibitor on Hormone Profiles in College-Age Men

Abstract: The purpose of this study was to determine the effects of an alleged aromatase and 5-α reductase inhibitor (AI) on strength, body composition, and hormonal profiles in resistance-trained men. Thirty resistance-trained men were randomly assigned in a double-blind manner to ingest 500 mg of either a placebo (PL) or AI once per day for 8 wk. Participants participated in a 4-d/wk resistance-training program for 8 wk. At Weeks 0, 4, and 8, body composition, 1-repetition-maximum (1RM) bench press and leg press, musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 24 publications
3
66
0
Order By: Relevance
“…DHT levels were reduced in the fenugreek group. Other studies demonstrate that fenugreek either causes no change or slightly increases testosterone in men have been for those with an already normal testosterone at baseline [219,220]. In other words, it is an unpredictable supplement in the area of TRT.…”
Section: Fenugreek (Trigonella Foenum-graecum)mentioning
confidence: 89%
See 1 more Smart Citation
“…DHT levels were reduced in the fenugreek group. Other studies demonstrate that fenugreek either causes no change or slightly increases testosterone in men have been for those with an already normal testosterone at baseline [219,220]. In other words, it is an unpredictable supplement in the area of TRT.…”
Section: Fenugreek (Trigonella Foenum-graecum)mentioning
confidence: 89%
“…It is usually characterized as an "alternative medicine" by some individuals and reviews [220], some may assume this is a dietary supplement, and there are many companies that sell "yohimbe" or tout that they sell "yohimbine HCL." The positive data with the drug or compound derived from this tree, yohimbine hydrochloride, came from European and other studies at a total of 5-10 mg per day (divided doses) [230].…”
Section: Yohimbine Hydrochloride (Not Really a Dietary Supplement Or mentioning
confidence: 99%
“…In addition, the plasma concentration of testosterone (T) and sperm concentrations were nearly 50% lower in the treated group of rabbits. Additionally, a recent, double blind, clinical study involving healthy, collegeaged men given fenugreek in a dose of 500 mg once daily for 8 weeks showed a significant effect in lowering body fat mass and did not lower the bioavailable and total serum T at week 8 compared to the baseline reading (Wilborn et al, 2010). This is also because, more recently, a protective effect has been reported for fenugreek not only in the case of carbofuraninhibited spermatogenesis but also in testes weight and histopath ological abnormalities induced by carbofuran exposure (Sakr and Shalaby, 2014).…”
Section: Effect On Fertility and Other Reproductive Effectsmentioning
confidence: 95%
“…The basis for this androgenic activity may be due to the fact that Trigonella foenum-graecum seeds contain soluble steroidal saponins, specifically furostanol glycosides, which are responsible for complexing cholesterol in the cell membrane [910]. Other studies have found that Trigonella foenum-graecum increases testosterone and free testosterone, suggesting that it may be an incomplete 5-alpha reductase and aromatase inhibitor [11]. In this study, we investigated the efficacy and safety of a mixed extract of Trigonella foenum-graecum seed and Lespedeza cuneata (TFGL) for the treatment of TDS.…”
Section: Introductionmentioning
confidence: 99%